KREDIBILITAS KEPEMIMPINAN KEPALA SEKOLAH UNTUK MENINGKATKAN PROFESIONALISME GURU - Zainul Ilyas (MIDA : Jurnal Pendidikan Dasar Islam, 2022)
Abstract This research huas the aim to see: (1) the principal function leadership in increase teacher professionalism, (2) the application of a modern leadership style to the principal of the MI Nurul Islam Alaspandan, Pakuniran, Probolinggo, East Java,(3) the importance of the principal’s credibity for improve teacher professionalism, this recearch is a qualitative descriptive. Data retrieved vis using observing, interviewing, as well as documenting. Checking the validity data is carried out through the following processes: checking the data against information from interviews with observing and documentation. This result indicates thay the lack of credibility of the leadership of the MI Nurul Islam principal resulted in improfessional teacher performance in teaching students, so it was necessary to apply a leadership role and modern leadership style so that the principal of MI Nurul Islam had a high leadership attitude, credibility to influence subordinates to do their jobs, properly, including, improve the professionalism of teachers to carry out their work duties as educators. Keywords: Leadership Credibility, Principal, Teacher Professionalism Abstrak Penelitian ini tujuannya guna mengetahui: (1) peran kepemimpinan kepala sekolah untuk peningkatan profesionalism guru, (2) penerapan gaya kepemimpinan modern pada kepala sekolah MI. Nurul Islam Alaspandan, Pakuniran, Probolinggo, Jawa Timur, (3) pentingnya kredibilitas kepala sekolah guna peningkatan profesionalisme guru. Penelitian ini yakni penelitian deskriptif kualitatif. Cara mengumpulkan data dijalankan melalui teknik observasi, wawancara, serta dokumentasi. Pengecekan absah data dilaksanakan melalui cara: pengecekan data terhadap informasi pada hasil wawancara, observasi maupun dokumentasi. Hasil penelitiannya memperlihatkan bahwasanya kurangnya kredibilitas kepemimpina kepala sekolah MI. Nurul Islam mengakibatkan kinerja guru tidak profesional dalam mengajar siswa, sehingga perlu diterapkan peran kepemimpinan dan gaya kepemimpinan modern agar kepala sekolah MI. Nurul Islam memilki kredibilitas kepemimpinan yang tinggi untuk memberi pengaruh pada bawahannya guna menjalankan kinerja mereka secara baik, termasuk meningkatkan profesionalisme guru dalam melaksanakan tugasnya sebagai pendidik. Kata kunci: Kredibilitas Kepemimpinan, Kepala Sekolah, Profesionalisme Guru